2019
DOI: 10.1002/mc.23107
|View full text |Cite
|
Sign up to set email alerts
|

miR‐210‐3p mediates metabolic adaptation and sustains DNA damage repair of resistant colon cancer cells to treatment with 5‐fluorouracil

Abstract: Chemoresistance is the primary cause of chemotherapy failure. Compelling evidence shows that micro RNAs (miRNAs) contribute to reprogram cancer cells toward a resistant phenotype. We investigate the role of miRNAs in the response to acute treatment with 5‐FU in colon cancer‐resistant cells. We performed a global gene expression profile for the entire miRNA genome and found a change in the expression of four miRNAs following acute treatment with 5‐FU. Among them, we focused on miR‐210‐3p, previously described a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Similarly, exosome-mediated transfer of miR-210-3p promotes lung cancer cell invasion by activating STAT3 signaling-induced EMT 27 . In colon cancer, miR-210-3p was reported to sustain DNA damage repair by metabolic adaptation 28 . Moreover, miR-210-3p is predictive of clear-cell renal cell carcinoma recurrence, pointing to potential utility as biomarkers 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, exosome-mediated transfer of miR-210-3p promotes lung cancer cell invasion by activating STAT3 signaling-induced EMT 27 . In colon cancer, miR-210-3p was reported to sustain DNA damage repair by metabolic adaptation 28 . Moreover, miR-210-3p is predictive of clear-cell renal cell carcinoma recurrence, pointing to potential utility as biomarkers 29 .…”
Section: Discussionmentioning
confidence: 99%
“…MiR-210 is a hypoxia-induced miRNA [77,78] and associated with radio-resistance in lung cancer [79]. Moreover, miR-210-3p was shown to be downregulated in colorectal cancer cells treated with 5-fluorouracil (5-FU), leading to an adaptation of cancer cells during treatment and enhancing chemotherapy resistance [80]. While the role of miR-210 is well studied during hypoxia, cancer progression and therapy, potential miRNA-independent functions of its host gene MIR210HG are less studied.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been found that the number of miRNAs regulated by HIF-1α mediates changes in cell metabolism [51], and the most studied hypoxia-induced miRNA is miR-210 [52,53]. HIF-1α-induced miR-210 is observed in many cell types, and it has been described as being involved in broad cancer pathologies, including DNA repair [54], survival [55], proliferation [56], metastasis [57], epithelial-mesenchymal transition (EMT) [58], angiogenesis [59], and radioresistance [60]. In oropharyngeal squamous cell carcinomas (OPSCC), iron-sulfur cluster assembly protein (ISCU) has been confirmed as a target of the HIF-1α-induced miR-210 [38].…”
Section: Mir-210mentioning
confidence: 99%